Co-occurrence of blaNDM–1 and mcr-9 in a Conjugative IncHI2/HI2A Plasmid From a Bloodstream Infection-Causing Carbapenem-Resistant Klebsiella pneumoniae - Liu, Zhou; Hang, Xiubing; Xiao, Xiao; Chu, Wenwen; Li, Xin; Liu, Yangyang; Li, Xi; Zhou, Qiang; Li, Jiabin (Frontiers in Microbiology, 2021)
Spread of the carbapenemase-encoding and mobilized colistin resistance (mcr) genes among Enterobacteriales poses a great threat to global public health, especially when the both genes are transferred by a single plasmid. Here, we identified a blaNDM-1- and mcr-9-co-encoding plasmid harbored by a clinical isolate of Klebsiella pneumoniae (KPN710429). KPN710429 was recovered from a blood sample from an inpatient in a tertiary hospital in China, and antimicrobial susceptibility testing showed that it was multidrug-resistant and only susceptible to aztreonam, colistin, and tigecycline. KPN710429 belongs to sequence type (ST) 1308 and capsular serotype KL144. The string test of KPN710429 was negative, and this strain didn’t exhibit a hypervirulent phenotype according to serum-killing and Galleria mellonella lethality assessments. Whole-genome sequencing revealed the KPN710429 genome comprises a single chromosome and three plasmids. All virulence associated genes were harboured by chromosome. Most of its antimicrobial resistance genes, including blaNDM-1 and mcr-9 were carried by plasmid pK701429_2, belonging to the incompatibility (Inc) HI2/HI2A group and ST1. Comparative genomics assays indicates that pK710429_2 could be a hybrid plasmid, formed by a Tn6696-like blaNDM-1 region inserting into a mcr-9-positive-IncHI2/HI2A plasmid. pK710429_2 contained the conjugative transfer gene regions, Tra1 and Tra2, with some structural variations, and conjugation assays revealed that pK710429_2 was transferable. Although pK710429_2 lacked the qseB-qseC regulatory genes, mcr-9 expression was upregulated after pretreatment with colistin for 6 h, leading to colistin resistance in KPN710429. To our knowledge, this is the first report of a blaNDM-1- and mcr-9-co-encoding transferable plasmid harbored by a bloodstream-infection-causing K. pneumoniae strain in China. Effective surveillance should be implemented to assess the prevalence of the plasmid co-harbouring carbapenemase-encoding gene and mcr-9.